Pembuatan Aplikasi Input Data Laboratorium Menggunakan Microsoft Access - Wandi Sujatmiko; Nurbiah Nurbiah; Rofianto Rofianto; Pratama Muhridan (Mars: Jurnal Teknik Mesin, Industri, Elektro Dan Ilmu Komputer, 2025)
With the increasing development of society, information is an important tool today. Information forces every person, both individuals and groups, both private and government, to calculate the information system that will be implemented in order to remain competitive in the era of globalization. In this case, the implementation of the right strategy allows every government agency to further improve services. In addition, the rapid advancement of information technology, but the lack of proper utilization. In general, the problems faced in the Information Technology Study Program Laboratory of Aisyiyah Pontianak Polytechnic are the suboptimal service of the inventory system where laboratory data is still manual so that the search time for equipment takes a long time. In instrumentation maintenance if it is still manual, it will be difficult to find out how many hours the equipment has been used and how many times it has been damaged. Along with the progress of Information Technology development, globalization is also becoming increasingly rapid. The specific objective of implementing the use of applications related to the theory of the concept of the course given to students. Analytical survey method with a Cross Sectional approach. The qualitative research design used is Phenomenological Research. The results of this study can improve the knowledge and skills of students, in improving knowledge in the field of Information Technology. Promoting the information technology study program at the Aisyiyah Pontianak Polytechnic.